Male reproductive system and spermatogenesis in the deep water crab Charyhdis smithii McLeay (Brachyura : Portunidae) - Balasubrahmanian, C P; Suseelan, C (Indian Journal of Fisheries, 2011)
Morphology of male reproductive tract and spermatogenesis of the potentiallycommercial deep water crab Charybdis smithii were studied in specimens obtainedduring the cruises of Fishery Oceanographic Research Vessel Sagar Sampada inthe Indian seas. Male reproductive tract is composed of testis, vasa deferentia,ejaculatory duct and external penis. Vas deferens is classified into anterior vasdeferens (AVD), middle vas deferens (MVD) and posterior vas deferens (PVD). Thetubular testis comprises numerous acini or seminiferous lobules arranged aroundcentral seminiferous duct. The spermatogenesis involves the progressive reductionof cjftoplasm and only one developmental stage was found in one seminiferouslobule at a time. The simple ellopsid spermatosphores are lodged in the AVD.The epithelial cells in the proximal portion of AVD are cuboidal whereas distalportion of AVD has columnar epithelial cells.